2023
DOI: 10.3390/toxics11040389
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and Risk Assessment to Airborne dl-PCBs and Dioxins in the Population Living in the Neighborhood of a Cement Plant: A Pilot Study in the Valencian Region of Spain

Abstract: Emissions from cement manufacturing facilities may increase health risks in nearby populations. For this reason, dioxin-like PCB (dl-PCB), polychlorinated dibenzo-p-dioxin (PCDD), and polychlorinated dibenzofuran (PCDF) concentrations in PM10 samples were assessed in the vicinity of a cement manufacturing plant located in the Valencian Region (eastern Spain). The total concentrations of the sum of dl-PCBs, PCDDs, and PCDFs ranged between 1.85 and 42.53 fg TEQ/m3 at the assessed stations. The average daily inha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Cheruiyot et al [76] observed that MSWIs utilizing activated carbon injection exhibited lower EF of 0.711 µg I-TEQ tonwaste -1 . Pham et al [77] reported the EF ranging from 0.011 -374 ng TEQ kg-waste -1 while recently, Ruiz et al [78] reported the lower EF of 1.85 ng TEQ kg-waste -1 . The comparison of our EF findings with Pham et al [77] and Ruiz et al [78] supports the hypothesis highlighted by Cheruiyot et al [76] that the combination of dry scrubber and baghouse is effective for simultaneous reduction of EF in flue gas emissions.…”
Section: Pcdd/fs Emission Factors and Potential Released To The Envir...mentioning
confidence: 99%
“…Cheruiyot et al [76] observed that MSWIs utilizing activated carbon injection exhibited lower EF of 0.711 µg I-TEQ tonwaste -1 . Pham et al [77] reported the EF ranging from 0.011 -374 ng TEQ kg-waste -1 while recently, Ruiz et al [78] reported the lower EF of 1.85 ng TEQ kg-waste -1 . The comparison of our EF findings with Pham et al [77] and Ruiz et al [78] supports the hypothesis highlighted by Cheruiyot et al [76] that the combination of dry scrubber and baghouse is effective for simultaneous reduction of EF in flue gas emissions.…”
Section: Pcdd/fs Emission Factors and Potential Released To The Envir...mentioning
confidence: 99%